Development of Chinese language application in learning as a second language for Malaysian - Mahamad, S. (Institute of Electrical and Electronics Engineers Inc., 2016)
With the booming of mobile technologies and Internet connection nowadays, the mobile applications are become more popular. Unlike Malaysia, mobile learning technology still not widely used in the education system as compare to developing countries where they had emerged into mobile learning technology in school. Hence, the main objective of this project is to encourage and support the process of learning Chinese language among young children who use Chinese as their second language at their own pace anytime anywhere by develop mobile learning application. The application will include learning, exercise and also performance evaluation of the learners in interactive way. Thus, they will expose to the mobile technology learning at the early age with interesting play and learn application that will give excitement in learning the language. Indirectly, this mobile learning application also helps to boost the performance of the learners in learning a new language. Â© 2016 IEEE.